Redistributive Preferences, Redistribution and Inequality: Evidence from a Panel of OECD Countries - Andreas Kuhn (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2012)
This paper describes individuals' inequality perceptions, distributional norms, and redistributive preferences in a panel of OECD countries, primarily focusing on the association between these subjective measures and the effective level of inequality and redistribution. Not surprisingly, the effective level of redistribution (after tax-and-transfer inequality) is positively (negatively) correlated with redistributive preferences. There is also evidence showing that the subjective and objective dimension of inequality and redistribution are, at least partially, linked with individuals' political preferences and their voting behavior. The association between objective and subjective measures of inequality and redistribution vanishes, however, once more fundamental country characteristics are taken into account. This suggests that these characteristics explain both redistributive preferences as well as the effective level of redistribution and after tax-and-transfer inequality.
Keywords: D31; D63; J31; 330; inequality perceptions; distributional norms; redistributive preferences; inequality; redistribution; political preferences